2023
DOI: 10.1007/s10439-023-03185-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of In Vivo Skin Anisotropy Using Elastic Wave Measurements and Bayesian Modelling

Abstract: In vivo skin exhibits viscoelastic, hyper-elastic and non-linear characteristics. It is under a constant state of non-equibiaxial tension in its natural configuration and is reinforced with oriented collagen fibers, which gives rise to anisotropic behaviour. Understanding the complex mechanical behaviour of skin has relevance across many sectors including pharmaceuticals, cosmetics and surgery. However, there is a dearth of quality data characterizing the anisotropy of human skin in vivo. The data available in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For simplicity of implementation and interpretation, the skin growth in this study was modelled to be transversely isotropic. This is motivated by clinical observations of tissue expansion in paediatric patients [13] and supported by our previous work, which indicated that younger patients have more isotropic skin tension [25]. Han et al relaxed this assumption and presented an anisotropic version of this model containing two growth rates for the transverse and longitudinal directions [29].…”
Section: Finite Element Modellingmentioning
confidence: 76%
See 1 more Smart Citation
“…For simplicity of implementation and interpretation, the skin growth in this study was modelled to be transversely isotropic. This is motivated by clinical observations of tissue expansion in paediatric patients [13] and supported by our previous work, which indicated that younger patients have more isotropic skin tension [25]. Han et al relaxed this assumption and presented an anisotropic version of this model containing two growth rates for the transverse and longitudinal directions [29].…”
Section: Finite Element Modellingmentioning
confidence: 76%
“…The goal of this study is to present a non-invasive method to measure important material properties of the skin, including natural pre-stretch, stiffness, and growth rate, and to predict the quantity of skin growth 7 days after expansion. Motivated by our previous work [25] [26], a non-invasive wave propagation technique is used in the following procedure:…”
Section: Introductionmentioning
confidence: 99%